Influence of Risk Assessment on Performance of SME Projects in Machakos County, Kenya - Mbuva, Peninnah Mbithe; Rambo, Charles, M.; Oketch, Timothy (European Scientific Journal, ESJ, 2018)
Small and medium enterprise projects play a major role in most economies in economic growth and development by creating employment opportunities to many people and as a source of technological innovation to create new products and eradication of poverty. Although their contribution in economic growth is indisputable, provocative argument on factors influencing their performance has remained unsolved to date. The purpose of this study was to determine the extent to which risk assessment influence performance of SME projects in Machakos County. The study applied pragmatism philosophical approach and descriptive survey research design. It tested the hypothesis at 95% confidence level which stated that risk assessment does not significantly influence performance of small and medium enterprise projects in Machakos County. The study used multiple regressions model against a sample size of 265 selected from a population of 5311 small and medium enterprise projects in Machakos County using stratified and convenience sampling approach as guided by the Yamane (1967) formula. A structured questionnaire was used to collect data whereby drop and pick approach was used. The study finding revealed that majority of the risk assessment components were positively supported by the respondents and their response mean was above 3.50, composite mean. Inferential statistics depicted that risk identification, prioritization and managing change significantly influenced financial performance with β=.102(p=0.016) and β=.092(p=0.012) respectively whereas organizational goals and objectives had insignificant influence with β=.031(p=0.366). Further, risk identification and prioritization significantly influenced non-financial performance with β=.104(p=0.017) whereas organizational goals and objectives and managing change had insignificant influence with β=.020(p=0.574) and β=.054(p=0.184) respectively. Management of SME projects should ensure the significant contribution by risk identification and prioritization towards performance in general is upheld with further endeavors to improve on the risk assessment components which have insignificant impact on performance. Further investigation is necessary to establish cause of risk assessment components influence disparities on both financial and non-financial performance perspectives.